Model Edukasi Kerelawanan di Sekolah Relawan - Ahmad M Syarif (Umbara, 2021)
This study describes Sekolah Relawan, a Non-Governmental Organization (NGO), whose activities focus on voluntarism education. This study explains the patterns and systems designed by the organization to educate the volunteers in order to achieve their competencies and characters. The educational model of this organization being analyzed using the concept of organizational culture; while paying attention to the basic assumptions of the founder, the values being internalized, and the artifacts being built in the everyday life of the volunteers. This study applied qualitative method, and the data collection techniques include interviews, participant observations and secondary data study. This study suggests that Sekolah Relawan as an NGO builds its sustainability of its educational system through ideas, knowledge, human resources, and funding. Voluntary education by the Sekolah Relawan delivered in stages, starting from education for beginners to experienced volunteers. This model of staged education has affected volunteer’s loyalty and program development, and organizational sustainability of the organization.